2022
DOI: 10.1186/s12906-022-03707-w
|View full text |Cite
|
Sign up to set email alerts
|

Alpinia officinarum Rhizome ameliorates the UVB induced photoaging through attenuating the phosphorylation of AKT and ERK

Abstract: Background Chronic ultraviolet (UV) exposure is one of the major external factors in skin aging, and repetitive UVB exposure induces extracellular matrix (ECM) damage as well as metabolic disease. Alpinia officinarum Rhizome (AOR) is a medicinal plant that has been traditionally used for treating rheumatism and whooping cough. However, the antiphotoaging effects of AOR remain unclear. We investigated the protective effects of water extracts of AOR (WEAOR) in terms of UVB-mediated ECM damage, wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
6
0
2
Order By: Relevance
“…Previous studies have suggested that several flavonoids, a kind of polyphenol, have exhibited strong anti-photoaging activity, such as delphinidin, genistein, phloretin and salidroside [33][34][35][36]. Interestingly, in our previous study, water extracts of Alpinia officinarum rhizome (WEAOR) were first revealed to have strong anti-photoaging activity, and kaempferide, a flavonoid, was determined to be a major constituent of WEAOR [30]. Thus, as follow-up research, the anti-photoaging activity of kaempferide and its underlying molecular mechanism was investigated in this study.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Previous studies have suggested that several flavonoids, a kind of polyphenol, have exhibited strong anti-photoaging activity, such as delphinidin, genistein, phloretin and salidroside [33][34][35][36]. Interestingly, in our previous study, water extracts of Alpinia officinarum rhizome (WEAOR) were first revealed to have strong anti-photoaging activity, and kaempferide, a flavonoid, was determined to be a major constituent of WEAOR [30]. Thus, as follow-up research, the anti-photoaging activity of kaempferide and its underlying molecular mechanism was investigated in this study.…”
Section: Discussionmentioning
confidence: 91%
“…The NIH-3T3 cells were lysed using a Tris-based protein lysis buffer [30] on ice for 1 h. After centrifuging (13,000× g, 4 °C, 15 min), the supernatants were used for Western blotting. Twenty micrograms of lysates were electrophoresed in sodium dodecyl sulfate (SDS) polyacrylamide gel and transferred to nitrocellulose membranes.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Ultraviolet radiation (UV) significantly accelerates the aging of the skin, with prolonged ultraviolet radiation-B (UVB) exposure frequently leading to the generation of reactive oxygen species (ROS) and harm to biomolecules like proteins and nucleic acids in the skin (Kammeyer and Luiten, 2015) [3]. The excessive exposure to UVB radiation also leads to the release of inflammatory cytokines such as Interleukin-6 (IL-6), Interleukin-1β (IL-1β), and Tumor Necrosis Factor-α (TNF-α) (Kim et al, 2012;Zhang, C et al, 2021;Jung et al, 2022) [4][5][6]. Melanocytes generate melanin as a protective response when subjected to UV rays.…”
Section: Introductionmentioning
confidence: 99%